Unlocking whistleblower protection: legal basis to be aware of - S. Abdülkerim-Osmanović; E. Kazić-Çakar (Law and Safety)
Hardly any negative social phenomenon is as specific as corruption, which creates an intriguing paradox in law. In particular, there is no phenomenon that is mentioned more often on a daily basis, even in colloquial speech, than corruption; there is no group of criminal offences (corruption) that the whole society knows more about; there is no legal topic on which legal scholars and practitioners are more in agreement on the criminal law consequences that corruption creates and are not willing to prevent it by creating various models of its prevention; and, again, many countries are constantly failing in the fight against it. Many people improve their perception of corruption only as the situation worsens. This paradox gives rise to a vision of corruption as an intractable, powerful giant, present since ancient times, with obvious obstacles that cannot be removed even in the most developed countries. Against this backdrop, it is important to ask, and this article attempts to answer, what role whistleblowers can play in the fight against corruption and whether their more effective protection can play an important role in protecting society from corruption. This study explores the recognition of whistleblowers' importance in these efforts, including the basis and nature of their legislative protection, through a legal analysis of selected regional and international legal sources that directly or indirectly refer to whistleblowers and their protection. The analysis shows that most of these sources indicate the importance of achieving the three whistleblower protection mechanisms. To achieve the above goals, regulatory and descriptive legal methods will be used.